Pembentukan Opini Publik Telkom University sebagai ‘The Best Private University in Indonesia’ - Dewi, Sonia; Christin, Maylanny; Imran, Ayub Ilfandy (Avant Garde, 2024)
In 2019, the Ministry of Education and Culture (Kemdikbud) announced the clustering of higher education institutions through the Kemdikbud website portal (http://klasterisasi-pt.kemendikbud.go.id). Based on the clustering results, Telkom University ranked 14th nationally and 1st as the best private university in Indonesia. In 2020, Kemdikbud again announced the clustering of higher education institutions with Telkom University ranking 17th nationally and still 1st as the best private university in Indonesia. Telkom University then used this result as the tagline ‘The Best Private University in Indonesia’ for institutional branding. Up to now, Telkom University continues to use the tagline ‘The Best Private University in Indonesia’. To maintain this branding, Telkom University implements a branding strategy through the formation of public opinion. This study employs a descriptive qualitative method and data collection through in-depth interviews. The results of the study show that Telkom University faces challenges in maintaining consistent branding amidst diverse public opinions. This makes it difficult to create a widely accepted brand image. To strengthen its claim as 'The Best Private University in Indonesia,' Telkom University improves transparency and engages in better interactions through social media while responding to constructive criticism. The branding claimed by Telkom University has received various responses, both positive and critical, indicating the need for further evaluation of the claim. Telkom University uses visual communication strategies and promotional activities that emphasize the university’s achievements to support its branding as ‘The Best Private University in Indonesia’.